Effect of Different Time of Earthing up on Growth and Yield Performances of Groundnut (Arachis hypogea L.) Varieties - Thilini, S.; Pradheeban, L.; Nishanthan, K. (University of Jaffna, 2019)
An experiment was conducted to assess the effect of different time of earthing up on growth and yield performances of groundnut (Arachis hypogea L.) varieties at the Faculty of Agriculture, Kilinochchi during the period of February to July 2018. Two factor factorial experiment was conducted in Randomized Complete Block Design (RCBD) with four replicates. Different dates of earthing up such as 23 days after (T1), 30 days after (T2) and 37 days after (T3) planting and five groundnut varieties; Lanka jumbo (V1), Tissa (V2), Tikiri (V3), Indi (V4), and ANK G1 (V5) were used as factors. The groundnut varieties were planted at the spacing of 45 cm × 15 cm and all other agronomic practices were done according to the recommendation of Department of Agriculture. The growth and yield parameters were recorded and shelling percentage was calculated. ANOVA and Duncan’s Multiple Range Test (DMRT) were performed to find out the significant differences among the treatment combinations. Growth parameters of groundnut varieties such as plant height, number of leaves and branches were not significantly differed among the varieties with duration of earthing up. The yield parameters such as fresh and dry pods weight per plant, 100 pods and seed weight and mature pods per plant were significantly differed among the duration of earthing up and also among the varieties and the highest records in T3 treatment in all varieties. There was no interaction effect among earthing up period and varieties. The highest shelling percentage of 84 % was observed in groundnut variety Lanka jumbo under the T3. The highest yield was obtained from T3 treatment in each variety and among the varieties; Lanka jumbo gave the highest yield. It can be concluded that 37 days after earthing up and Lanka jumbo can be selected as suitable treatment combination to obtain the highest yield from groundnut in Kilinochchi District.
Keywords: Earthing up; Groundnut; Shelling percentage; Yield.